Assessment of Climate Change Impacts on Chilling and Forcing for the Main Fresh Fruit Regions in Portugal - Fraga, Helder; Santos, João A. (Frontiers in Plant Science, 2021)
Air temperature plays a major role in the growth cycle of fruit trees. Chilling and forcing are two of the main mechanisms that drive temperate fruit development, namely dormancy and active plant development. Given the strong sensitivity of these crops to air temperature and the foreseeable warming under future climates, it becomes imperative to analyze climate change impacts for fruit trees. The fruit sector in Portugal has risen significantly over the last decades, gaining increasing importance both internally and through exports. The present research assesses the impacts of climate change on the chilling and forcing for economically relevant fruit trees in Portugal, namely apples, oranges, pears and plums. To assess temperate fruit chilling and forcing conditions, the chilling portions (CP) and growing degree-hours (GDH) were computed over Portugal, for the recent-past (1989–2005) and future (2021–2080) periods, following two anthropogenic radiative forcing scenarios (RCP4.5 and RCP8.5). Future climate data were obtained from four regional-global climate model pairs to account for model uncertainties. Bias-correction methodologies were also applied. A spatial analysis over the main regions with PDO “Protected Denomination of Origin” or PDI “Protected Geographical Indication” of origin of each fruit tree was performed. Future projections show a clear decrease in chilling for all regions and fruit types in Portugal. Nonetheless, given the current chilling values in Portugal and the relative importance of chilling accumulation for each fruit type, these changes are more significant for certain varieties of apples than for other types of fruit. Regarding forcing, the future projections highlight an increase in its values throughout the different fruit tree regions in Portugal, which should lead to earlier phenological timings. These changes may bring limitations to some of the most important Portuguese temperate fruit regions. The planning of suitable adaptation measures against these threats is critical to control the risk of exposure to climate change, thus warranting the future sustainability of the Portuguese fruit sector, which is currently of foremost relevance to the national food security and economy.